A Dust-Enshrouded Tidal Disruption Event in a Luminous Infared Galaxy. Issue Volume 14:Issue S339(2018) (November 2017) - Mattila, S.
Abstract: This paper presented the discovery of an energetic nuclear transient from near-infrared monitoring of nearby starburst and luminous infrared galaxies. The transient radiated at least 1.5E+52 erg in the infrared but remained elusive at optical and X-ray wavelengths. We interpret its properties as arising from a stellar tidal disruption event (TDE) close to a supermassive black hole. Much of its emission must have been reprocessed by dense gas and re-radiated at infrared wavelengths by dust, suggesting a way for reducing the tension between theoretical luminosity predictions and observations of TDEs. Such events are not detectable by optical, UV or soft X-ray observations, and might represent just the tip of the iceberg of a missed TDE population in the local Universe. That population could be more numerous at higher redshifts where luminous infrared galaxies are more common.